Blast-off simulation sebagai alternatif media pembelajaran siswa dalam mempelajari mekanika gerak roket berbasis matlab - Alpi Mahisha Nugraha; Nurullaeli Nurullaeli (Navigation Physics : Journal of Physics Education, 2019)
Blast-off or rocket launcher is a physics phenomena about mechanical of motion specially momentum principal. Unlike other flying objects like blimps and airplanes, blass-off uses the principle of changing momentum as a driving force to able fly in the air. The definition of force is a rate of changing momentum, the definition is illustrated by first-order differential equation which can be solved analytically or numerically. Unfortunately, during class learning, the equation is only used to solve collision problems instead of being used to explain blast-off phenomena which is very interesting to learn mostly. Moreover, if the explanation in the class uses visual media such as Graphic User Interface (GUI). Blast-off simulation is designed from the solving of the first differential numerically, and then the algorithm is compiled using Matlab aplication with an output in the form of a GUI so students become more interested in learning momentum and learning effectiveness will be incrised.